Э. Р. фон Штерн и создание северопричерноморской школы античной археологии - Кузьмищев, О.Г. (Археологія і давня історія України, 2019)
Рассмотрено влияние Э. Р. фон Штерна на формирование школы северопричерноморской античной археологии, где были такие исследователи
как Б. В. Фармаковский, М. Ф. Болтенко и др. Ernst R. von Stern (1859—1924) was one of the
prominent historians of antiquity in the late XIX —
early XX century, who participated in the development of Classic archaeology of the Northern Black Sea region.
The article discusses the role of E. R. von Stern in the creation of the school of Classic archaeology, which
was based on the Novorossiisk University in Odessa and the Odessa Society of History and Antiquities, in
particular the museum of that society, as well as the contribution of E. R. von Stern in education of native
archaeologists and historians. E. R. von Stern, having considerable experience
in teaching, understood the importance of educating young professional personnel. As a result, due to a long
and systematic work, E. R. von Stern was able to create a scientific school of his followers.
Among the students of E. R. von Stern were those who later became well-known scholars, connecting their
lives with history and archaeology. In particular, the scientific career of B. V. Farmakovskyi (1870—1928),
an outstanding archaeologist, a long-term researcher of Olbia, was largely formed thanks to the pedagogical
talent of E. R. von Stern. The most known students of E. R. von Stern, except
B. V. Farmakovskyi, were also M. I. Mandes (1866—1934), E. G. Kagarov (1882—1942) and M. F. Boltenko (1888—1959).